LITERASI KETAHANAN PANGAN BERBASIS PHOTOVOICE DENGAN MODEL GI TERHADAP KEPEDULIAN DAN HASIL KARYA TULIS ILMIAH KIR - Purnami, Luh Eka Sri; Puspawati, Dewa Ayu; Yuwono, Cornelius Sri Murdo (Jurnal Santiaji Pendidikan (JSP), 2018)
Food security has become a concern at national and international scope. Recently, food security has not been widely integrated into education, so the impact is students’ low awareness on it. One solution to overcome the situation is to raise food security literacy by using photovoice through Group Investigation learning model. The purpose of this study is to analyze the awareness and score of students’ scientific paper through the aforementioned methods. Quasi-Experimental Design with Nonequivalent Control Group Design was used. The population was all students of Youth Science Group in X class of SMA (SLUA) ​​Saraswati 1 Denpasar in the second semester of academic year 2015/2016. Sample used were students of X MIA 1 as a control and X MIA 2 as an experimental class. Data collection technique for gaining awareness of students was distributing questionnaires of awareness Assessment results of scientific paper was then assessed by using rubric. Data analysis technique usedwas Mann-Whitney U test. The results of quantitative research show that there wasa difference on the awareness and score of scientific paper between the control and the experimental class with the significant degree of p=0.000<0.05. In conclusion,the food security literacy based on photovoice in Group Investigation learning model increased the awareness and score of students’ scientific paper.